Prospective class teachers’ attitude profiles towards learning and teaching mathematics - Tomi Kärki; Harry Silfverberg (Sweden, 2022)
In our study, we measured prospective class teachers’ (n = 175) attitudes, on one hand, towards learning mathematics and, on the other hand, towards teaching mathematics. We used a questionnaire called ALM (Attitudes toward Learning Mathematics) developed by Wong and Chen (2012), and we constructed another questionnaire called ATM (Attitudes toward Teaching Mathematics) by modifying the items of ALM to focus on teaching instead of learning. Prospectiveteachers’ attitude profiles towards learning and teaching mathematics were compared with each other. In general, their attitudes were quite positive, and the attitudes towards teaching were more positive than towards learning. Component-wise differences between ALM and ATM were found.We also compared attitude profiles between two class teacher programs. Prospective teacher’sattitudes in a program with emphasis on mathematics and natural sciences were more positive than in a non-mathematically-focused program.
Nordic Research in Mathematics Education. Papers of NORMA 17: The Eighth Nordic Conference on Mathematics Education, Stockholm, May 30-June 2, 2017